The walentaite group and the description of a new member, alcantarillaite, from the Alcantarilla mine, Belalcázar, Córdoba, Andalusia, Spain. (18th June 2020) - Grey, Ian E.; Hochleitner, Rupert; Rewitzer, Christian; Riboldi-Tunnicliffe, Alan; Kampf, Anthony R.; MacRae, Colin M.; Mumme, W. Gus; Kaliwoda, Melanie; Friis, Henrik; Martin, Carlos U.
Abstract: The general structural formula for the walentaite group is [(( A 1 y A 1'1– y ), A 2)(H2 O) n ][ Bx ( As 2)2– x ( As 3) M 1( M 2)2 ( T O4 )2 (O, OH)7 ], based on heteropolyhedral layers of configuration [ M 1( M 2)2 ( T O4 )2 (O, OH)6 ], with surface-coordinated species at the B, As 2 and As 3 sites, and with interlayer hydrated cation groups centred at the A sites. The group is divided into walentaite and halilsarpite subgroups based on T = P 5+ and As 5+, respectively. Alcantarillaite, (IMA2019-072), [Fe 3+ 0.5 □0.5 (H2 O)4 ][CaAs 3+ 2 (Fe 3+ 2.5 W 6+ 0.5 )(AsO4 )2 O7 ], is a new member of the walentaite group from the Alcantarilla wolframite mine, Belalcázar, Córdoba, Andalusia, Spain. It occurs most commonly as lemon-yellow fillings together with massive scorodite in fissures and cracks in quartz adjacent to löllingite. It is also found as tiny yellow rosettes lining vugs and as spheroids of ultrathin blades. It is associated with scorodite, pharmacosiderite, ferberite and schneiderhöhnite. Optically it is biaxial (–), with α = 1.703(calc), β = 1.800(5), γ = 1.850(5) and 2 V = 68(1)° (white light). Dispersion is r > v, moderate. The optical orientation is X = a, Y = c and Z = b . The calculated density is 3.06 g cm –3 . Electron microprobe analyses together with crystal structure refinement results gives the empirical formula [Fe 3+ 0.52 □0.48 (H2 O)4 ][(Ca0.44 K0.11 Na0.05 Fe 2+ 0.24 □0.42 )As 3+ 1.83 ][Fe 3+ 2.54 Al0.03 W 6+ 0.43 )((As0.65 P0.35 )O4 )2 O5.86 (OH)1.14 ]. Alcantarillaite is orthorhombic, with an average structure described in Imma, and with a = 24.038(8) Å, b = 7.444(3) Å, c = 10.387(3) Å, V = 1858.6(11) Å 3 and Z = 4. The structure ( wR obs = 0.078 for 651 reflections to a resolution of 0.91 Å) differs most significantly from other walentaite-group members in having an interlayer A 2 site occupied. Square-pyramidal polyhedra centred at the A 2 sites form edge-shared dimers, (Fe 3+ )2 O4 (H2 O)4 . The dimers share vertices with T O4 anions in the layers on either side to form 8-sided channels along [010] occupied by H2 O molecules.